SEMANTIC AMBIGUITY : A STUDY ON THE LEXICAL INTERPRETATION OF HOMONYMS AND HOMOGRAPHS IN DAILY COMMUNICATION - Juliana Tifani; Bernieke Anggita Ristia Damanik (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study investigates the role of homonyms and homographs as sources of semantic ambiguity in daily English communication. Semantic ambiguity occurs when words or phrases can be interpreted in more than one way, leading to misunderstandings in both spoken and written language. Focusing on lexical ambiguity, this research analyzes how homonyms words that share the same spelling and pronunciation but have different, unrelated meanings and homographs words that share spelling but differ in pronunciation and meaning contribute to communication breakdowns. Using a qualitative descriptive method, data were collected from real-life language use, highlighting how individuals interpret ambiguous words based on context. The findings show that without clear contextual cues, these lexical items often lead to misinterpretation. The study emphasizes the importance of context, background knowledge, and linguistic awareness in reducing ambiguity and promoting effective communication. It also suggests practical strategies for educators, learners, and speakers to navigate and resolve ambiguity in everyday language use.